Development in Malaysia: an overview - Md. Noon, Hazizan (Cengage Learning Asia Pte Ltd, 2013)
This book chapter analyses the development policies pursued under various administrations since the Mahathir era to the present-day administration of Tun Najib Abdul Razak. As a background, it discusses the history of Malaysia emphasizing on the various policies introduced and implemented prior to the Mahathir's administration.